2019
DOI: 10.1080/17522439.2019.1603320
|View full text |Cite
|
Sign up to set email alerts
|

How do people talk decades later about their crisis that we call psychosis? A qualitative study of the personal meaning-making process

Abstract: Psychosis refers to a severe mental state that often significantly affects the individual's life course. However, it remains unclear how people with the lived experiences themselves view these phenomena, as part of their life story. In order to evaluate this personal meaning-making process we conducted in-depth life-story interviews with 20 people who had been diagnosed with non-affective psychosis 10 to 23 years previously in one catchment area. 35% of them were still receiving mental health treatment, and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
(28 reference statements)
3
24
0
1
Order By: Relevance
“…However, they suggest that developmental trauma is only a cause of psychosis in one third of people who receive a psychosis diagnosis. The possibility that it is not a factor in all cases is consistent with the work of Romme et al (2009) and Bergström et al (2019), but these researchers reported that other severe stresses, some in adulthood, could also contribute to psychosis. It may be that a broader definition of trauma is needed to avoid missing important life adversities.…”
Section: What Therapies Work For Trauma Where People Have Experience Of Psychosis?supporting
confidence: 84%
“…However, they suggest that developmental trauma is only a cause of psychosis in one third of people who receive a psychosis diagnosis. The possibility that it is not a factor in all cases is consistent with the work of Romme et al (2009) and Bergström et al (2019), but these researchers reported that other severe stresses, some in adulthood, could also contribute to psychosis. It may be that a broader definition of trauma is needed to avoid missing important life adversities.…”
Section: What Therapies Work For Trauma Where People Have Experience Of Psychosis?supporting
confidence: 84%
“…In the second study I examine here, Bergström et al (2019) point out the importance of hearing from service users themselves about how they understand their difficulties. They suggest that clinical language can dominate when people are in treatment, making it harder to see how people make sense of their own experiences, and to offer them the kind of support that will be most helpful.…”
Section: Who Was Included In the Study?mentioning
confidence: 99%
“…As explained earlier, the Open Dialogue approach includes the principle of avoiding imposing any specific explanations of people's difficulties (including diagnosis), and enabling service users and their social network members to be more in control. Bergström et al (2019) set out to find out what service users thought about their experiences some years after their initial treatment with the Open Dialogue approach. Bergström et al (2019) suggest that even those close to someone may try to impose their own explanations onto people's difficulties.…”
Section: Who Was Included In the Study?mentioning
confidence: 99%
See 2 more Smart Citations